The Effect of Turbulence on Two-Fluid Flow and Heat Transfer in Continuous Steel Casting Process - Mookum, T.; Wiwatanapataphee, B.; Wu, Yong Hong (WSEAS Press, 2011)
In this paper, we develop a mathematical model to study the coupled turbulent two-fluid flow and heat transfer process in continuous steel casting. The complete set of field equations are established. The turbulence effect on a flow pattern of molten steel and lubricant oil, meniscus shape and temperature field as well as solidification are presented in the paper.